Pregled uporabe zračnega laserskega skeniranja površja v gozdarstvu - Kobal, Milan (Gozdarski vestnik, 2014)
Airborne Laser Scanning is a remote sensing method that is being used in different spatial sciences. It is becoming more and more interesting also in Forestry. In forestry ALS can be used for valuation of directly measurable stand parameters (e.g. tree height) and for indirectly executed stand characteristics (e.g. growing stock). Increasing trend can be noticed in applications of ALS data in time series studies. This article describes basics of ALS data processing. Different spatial scales of ALS data processing are presented (e.g. landscape, forest stand, and single tree). All the presented examples refer to the area of dinaric silver fir % European beech forests Omphalodo-Fagetum s.lat., FMU Leskova dolina.
Keywords: zračno lasersko skeniranje; lidar; airborne laser scanning; digital elevation model; digitalni model reliefa; forest stand structure; zgradba sestojev; jelovo-bukovi gozdovi